An adaptive algorithm for searching in flow tables of openflow switches - Gopakumar, R.; Unni, A. M.; Dhipin, V. P. (2015 39th National Systems Conference (NSC), 2015)
Software Defined Networking (SDN) is the new paradigm in computer networking industry which changes the present distributed architecture to a centralized one. The three main components of this centralized architecture are Openflow controller, Openflow channel and Openflow switches. Openflow controller is the centralized controlling unit which communicates with openflow switchies via openflow channel according to Openflow protocol specifications. OpenFlow enabled/only switches are the back bone of Software Defined Networking architecture. OpenFlow controllers writes the packet processing parameters necessary to match with an incoming packet and actions to be taken for a packet type in to the flow tables of an Openflow switch. Openflow protocol does not mandate to use any specific algorithm to search for matching flows in the flow tables. Here we analyzes the performance of 4 data searching algorithms and propose an adaptive algorithm considering load factor also as a parameter to reduce the searching time.